1994
DOI: 10.1111/j.1440-1754.1994.tb00564.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐Reactive protein as a diagnostic tool of sepsis in very immature babies

Abstract: Three hundred and nine septic screens were performed on 123 consecutively admitted infants of < 30 weeks gestation. As part of the septic screen, serial quantitative measurements of C-reactive protein (CRP) were performed daily until discontinuation of antibiotic therapy. Complete blood counts were performed daily for the first 2 days of each septic episode. The babies had a mean birth weight of 1035.8 g s.d. 273.2 and a mean gestational age of 27 weeks s.d. 1.8. A CRP level of 10 mg/L or above was considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 18 publications
2
25
1
Order By: Relevance
“…Serial measurements of CRP levels appear to have the best discriminatory value for predicting septicemia among the tests currently available in many hospital laboratories, and the ability to produce CRP does not appear to be affected by gestational age (8,377,426). Several studies have specifically addressed the utility of CRP screening in VLBW neonates, with the sensitivity of a CRP value greater than 1 mg/dl for blood culture-proven sepsis ranging from 48 to 63% when a single test is performed and from 84 to 90% when multiple CRP screens are performed over a 24-to 48-h period following onset of symptoms (77,487). In many studies, CRP has been shown to have higher sensitivity and negative predictive value than leukocyte indices such as the immature/total neutrophil ratio for predicting bacteremia (154).…”
Section: Use Of Adjunct Laboratory Tests To Predict Septicemiamentioning
confidence: 99%
“…Serial measurements of CRP levels appear to have the best discriminatory value for predicting septicemia among the tests currently available in many hospital laboratories, and the ability to produce CRP does not appear to be affected by gestational age (8,377,426). Several studies have specifically addressed the utility of CRP screening in VLBW neonates, with the sensitivity of a CRP value greater than 1 mg/dl for blood culture-proven sepsis ranging from 48 to 63% when a single test is performed and from 84 to 90% when multiple CRP screens are performed over a 24-to 48-h period following onset of symptoms (77,487). In many studies, CRP has been shown to have higher sensitivity and negative predictive value than leukocyte indices such as the immature/total neutrophil ratio for predicting bacteremia (154).…”
Section: Use Of Adjunct Laboratory Tests To Predict Septicemiamentioning
confidence: 99%
“…9,11 C-reactive protein (CRP) is an acute phase reactant that increases with infection and inflammation and is used as a screening tool for neonatal sepsis. [12][13][14] There is recent evidence that CRP may have a proinflammatory role in addition to being an inflammatory marker, [15][16][17] and high concentrations of CRP have been shown to correlate with mortality and organ failure in critically ill adults. 18 It is possible that CRP may be useful as a prognostic marker in ELBW infants.…”
Section: Introductionmentioning
confidence: 99%
“…The variability in the accuracy of leukocyte and CRP to predict sepsis is still remarkable. However, it is important to note that both tests are quite predictive of neonatal sepsis when measured serially (16)(17)(18)(19). Thus, these tests when repeated provide useful information when treating an infant with suspected sepsis but negative blood cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In this updated review, few articles published since 1994 that evaluated CRP and leukocyte parameters were identified (16)(17)(18)(19). The variability in the accuracy of leukocyte and CRP to predict sepsis is still remarkable.…”
Section: Discussionmentioning
confidence: 99%